3PC-004 Automation of parenteral nutrition elaboration in a hospital pharmacy service - Blanco-Dorado, S (Eur J Hosp Pharm, 2018)
BACKGROUND: Parenteral nutrition (PN) is a high-risk medication. For this reason quality control must be guaranteed. PURPOSE: To evaluate the impact of implementing an automated system (Exacta-Mix 2400(®) Baxa) on the quality of the elaboration of PN. MATERIAL AND METHODS: Retrospective study in which a comparative gravimetric control was performed between the PNs in the first week of December 2015 (manual procedure) and the same week one year later with the automated system. Gravimetric control is a strategy used for the quality control in the elaboration of PN. It consists of comparing the real weight with the theoretical weight (calculated according to the volume and density of each of its components). The gravimetric error was calculated as a percentage compared to the theoretical weight. Regulatory agencies establish an acceptable margin of error of 5%, and advise reducing it to 3%, especially in paediatric nutrition. The deviations from the theoretical weight and the percentage of preparations that exceeded 3% were analysed. For the comparison of means of deviation, a K-W test was performed using software R. Tricameral nutrition was excluded from the study because it is already elaborated and does not require manipulation. RESULTS: One hundred and fourty-four PNs (77 manuals and 77 automated) were analysed. The mean variation of the actual weight with respect to the theoretical weight was 3.37% and 0.73% with the manual and automated procedure respectively (p<0. 05). Forty-five PNs exceeded the margin of error of 3% and 12 PNs exceeded the margin of error of 5% with the manual procedure. None of the PNs made with Exacta-Mix 2400(®) Baxa exceeded the variation limit of 3%. CONCLUSION: Manual preparation of parenteral nutrition is associated with a greater gravimetric error due to human preparation. This is especially important in very low weight nutrition, such as neonatal nutrition. Automation means an increase in accuracy control and a decrease in the risk of exceeding acceptable limits. Despite the difficulties of implementing a new technological process, robotisation tends to become an essential in hospital pharmacy services and allows an improvement in the integral quality of care. REFERENCE AND/OR ACKNOWLEDGEMENTS: 1. Llop Talavera JM, et al. Automation of parenteral nutrition elaboration: adaptation to in force legislation. Nutr Hosp. 2006Mar–Apr;21(2):184–8. No conflict of interest